Prolactinoma-associated headache and dopamine agonist treatment. (June 2014) - Kallestrup, Mia-Maiken; Kasch, Helge; Østerby, Toke; Nielsen, Edith; Jensen, Troels S; Jørgensen, Jens OL
Aim: The aim of this article is to investigate the phenotype and etiology of prolactinoma-associated headache as well as present and discuss the plausible pain-relieving effect of dopamine agonist treatment. Methods: In this case-based audit we included 11 patients with prolactinomas and one patient with idiopathic hyperprolactinemia presenting with headache that subsequently improved or resolved after dopamine agonist treatment. Results: A significant ipsilateral location of tumor mass and reported headache symptoms was observed ( p = 0.018). After dopamine agonist treatment seven out of 12 patients became pain free within 2.5 months; after one year of treatment 11 out of 12 reported headache improvement or resolution. Average tumor volume reduction after treatment was 47 ± 22% during 9.5 ± 8.4 months of follow-up. There was no significant association between headache relief and tumor shrinkage ( p = 0.43) or normalization of serum prolactin ( p = 1.00), respectively. Conclusions: 1) The significant association between lateralization of tumor and headache suggests a mechanical origin of the headache, 2) headache responded to dopamine agonist treatment in most patients, and 3) our observations encourage future prospective controlled trials to investigate the role of hyperprolactinemia in the pathogenesis of headache as well as the therapeutic effects of dopamine agonists.